The Relationship of Workload with Nurses' job stress at Bhakti Husada Hospital Cikarang - Mutianingsih Mutianingsih; Noor Lusti Putri; Marini Iskandar; Farisa Fabia Putri; Nabila Nabila (Lembaga Pengembangan Kinerja Dosen, 2024)
Work stress is psychological or physical tension as a response to pressure from the work environment. Nurse work stress can occur if nurses in carrying out their duties receive a workload that exceeds their abilities so that nurses are unable to fulfill or complete their duties well. Nurses have higher stress levels than other professionals in hospitals.To determine the relationship between workload and work stress among nurses at Bhakti Husada Hospital, Cikarang. The research design uses quantitative descriptive correlation using a cross sectional approach. The population in this study were all nurses in the Bhakti Husada Cikaran Hospital inpatient room, totaling 58 people. The sampling technique uses total sampling, where the entire population is used as a research sample. Data collection was carried out using a questionnaire. The research results showed that 58.6% of nurses had a heavy workload. while the stress level of nurses was found to be 63.8% of nurses experiencing high stress. Statistical tests show that there is a significant relationship between workload and work stress (p value = 0.005). Workload is one of the factors that influences work stress in nurses. Nurses are expected to be able to provide support and motivation to each other so as to create a conducive work environment which can reduce work stress in nurses.